2017
DOI: 10.1080/15384047.2017.1281493
|View full text |Cite
|
Sign up to set email alerts
|

The association between circulating tumor cells and Epstein-Barr virus activation in patients with nasopharyngeal carcinoma

Abstract: Background: Circulating tumor cells (CTCs) and microemboli (CTM) are attracting increasing attention in medical biology and clinical practice. However, the clinical relevance of CTCs in nasopharyngeal carcinoma (NPC) has not yet been ascertained, and no study has focused on the influence of Epstein-Barr virus (EBV) status on CTCs in NPC patients. These issues were therefore examined. Methods: Peripheral blood samples were prospectively obtained from 33 NPC patients before treatment. CTCs and CTM were captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…CTC analysis based on cell size was conducted with reference to previous studies. 14 15 the blood was divided into two specimens. Each specimen was made to pass through a membrane with a pore size of 10 um, and two membranes were obtained.…”
Section: Separation and Identification Of Ctcsmentioning
confidence: 99%
“…CTC analysis based on cell size was conducted with reference to previous studies. 14 15 the blood was divided into two specimens. Each specimen was made to pass through a membrane with a pore size of 10 um, and two membranes were obtained.…”
Section: Separation and Identification Of Ctcsmentioning
confidence: 99%
“…14 CTCs and EBV DNA are predictive markers of NPC metastasis, 15 and EBV activation is associated with the number of NPC CTC. 16 Therefore, we speculate that EBV may participate in NPC metastasis through metastasis.…”
Section: Introductionmentioning
confidence: 92%
“…Clinical studies have shown that EBV-DNA levels were associated with CTC number in patients with NPC. 14,16 During tumor development, various types of cells are observed in the peripheral blood, such as CTCs and CTC clusters. In addition, the presence of disseminated tumor cells (DTCs) in the peripheral blood which are normally present in bone marrow is an important factor in metastasis development.…”
Section: Ebv Promotes Generation Of Npc Ctcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that CTCs, which could be dispersed into circulation system by primary and metastatic cancers, are closely correlated with recurrence and metastasis of several tumour types, including breast cancer ( 2 ), lung cancer ( 3 ), gastric cancer ( 4 ), head and neck cancers ( 5 7 ), as well as resistance to anti-tumour treatment. Additionally, it is of significant clinical guiding value in auxiliary diagnosis, therapeutic evaluation, recurrence and metastasis monitoring and prognostic assessment of tumour patients.…”
Section: Introductionmentioning
confidence: 99%